From the Green Room to the Court Room (And Back): Judicial Clarification of Ambiguity in WTO Law and the Effects on Subsequent Negotiations - James Flett (Oñati Socio-Legal Series)
The WTO provides an opportunity to observe the recent creation, development and operation of a "hard law" adjudicative legal system, with legal subjects of greatly varying degrees of power, embedded within an intensely political environment. Between these parallel political and legal communities there are numerous points of contact. At each point of contact one finds played out (or to be played out) and resolved, re-iteratively, the basic drama between power-based and rules-based approaches to disputes. An examination of the Dispute Settlement Understanding and of subsequent developments - from the particular perspective of a participant within the WTO legal system - suggests that the rules-based approach was initiated in a somewhat low profile manner. Once the process had been quietly booted-up, ambiguity and discretion embedded in the rules has been systematically crystallizing, under the influence of lawyers and adjudicators acting both in and out of the court room, so as to substantially further develop and consolidate a more complete rules-based operating system. This is something to which the Members themselves do not appear to have objected. In the long term, the fundamental driving motor for this process, which ultimately outweighs all other considerations, is a necessity recognised by all participants and their constituents – that is, legal security and predictability for firms engaged in international trade. However, the legitimacy of particular outcomes will ultimately continue to rest upon the rationality, reasonableness and openness of adjudicators and their judgments. This repetitive process of shared experience and palliative outcome is progressively binding the political and legal communities together in a shared fate. The process is proving remarkably successful, and may both serve as a model for (and have spill-over effects in) other areas of international law. Ultimately, the system's continued success depends upon jealously guarding the independence of adjudicators, including the process by which they are selected, as well as ensuring the availability of effective remedies.